Pengaturan Besaran Honorarium Sebagai Hak Notaris Terhadap Pembuatan Akta - Pramelia, L.N. Ria; Suyatna, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 03 (2024)DO - 10.24843/AC.2024.v09.i03.p06, 2024)
The aim of this research is to find out the regulations and limitation system regarding honorariums. Where Article 36 UUJN only regulates the maximum limit of honorarium. Based on this, a problem formulation was formulated, namely: 1) How is the meaning of honorarium in making deeds by a Notary? 2) What is the system for limiting the Notary's honorarium for making deeds? This research uses a normative legal research method which is carried out by taking a statutory approach (The Statue Approach) and a legal concept analysis approach (Analytical and Conceptual Approach). This paper focuses on empty norms contained in Article 36 UUJN which only regulates boundaries. maximum honorarium for Notaries without setting a minimum limit for honorarium. Therefore, it is necessary to amend the provisions of the norms of Article 36 UUJN so that the norm material contains provisions regarding the determination of the minimum limit for honorarium determined by the notary position organization, so that the determination of the professional organization for the notary position has binding force based on the Law. -Law the position of Notary and not give rise to unhealthy competition among Notaries.